Slovenska polivokalna romana s tematiko druge svetovne vojne - Smolej, Tone (Primerjalna književnost, 2015)
The paper discusses the novels The Record (Zapisnik) by Vladimir Kavčič and I Saw Her That Night (To noč sem jo videl) by Drago Jančar. An examination of their polyvocality is accompanied by a discussion of their sources and an analysis of the contemporary reception, based on previously unknown documents.
Keywords: Jančar, Drago; Kavčič, Vladimir; književnost in zgodovina; primerjalne študije; slovenska književnost; svetovna vojna 1939-1945; zgodovinski roman